CT findings are highly predictive for perforation in patients with diffuse large B-cell lymphoma involving the intestines. Issue 8 (3rd August 2018) - Sarid, Nadav; Sherban, Adi; Bendet, Achiude; Adam, Sharon; Herishanu, Yair; Perry, Chava; Avivi, Irit
Abstract: Patients with diffuse large B-cell lymphoma (DLBCL) presenting with intestinal involvement are prone to develop perforation. Identification of those who are at high risk for this complication would enable a rational-based decision regarding preemptive surgery. Although computed tomography (CT) is widely used at diagnosis, data regarding its ability to predict intestinal perforation are scanty. We performed a retrospective single-center study, including all consecutive DLBCL patients presented with intestinal involvement, assessing predictors for perforation with an emphasis on CT-related parameters. Forty-nine patients were included, 43 (88%) underwent CT scan at diagnosis. Ten patients (20%) developed intestinal perforation. A univariate regression analysis found increased risk among patients with a concentric, transmural lesion, and a longer involved intestinal segment. In conclusion, CT scan results can define patients with DLBCL and intestinal involvement who are at risk for perforation, suggesting that a preemptive surgical resection should be considered in these cases.